Motor-Imagery-Based Teleoperation of a Dual-Arm Robot Performing Manipulation Tasks - Liu, Yiliang; Su, Wenbin; Li, Zhijun; Shi, Guangming; Chu, Xiaoli; Kang, Yu; Shang, Weiwei (IEEE transactions on cognitive and developmental systems, 2019)
This paper proposes a brain-computer interface (BCI)-based teleoperation strategy for a dual-arm robot carrying a common object by multifingered hands. The BCI is based on motor imagery of the human brain, which utilizes common spatial pattern method to analyze the filtered electroencephalograph signals. Human intentions can be recognized and classified into the corresponding reference commands in task space for the robot according to phenomena of event-related synchronization/desynchronization, such that the object manipulation tasks guided by human user's mind can be achieved. Subsequently, a concise dynamics consisting of the dynamics of the robotic arms and the geometrical constraints between the end-effectors and the object is formulated for the coordinated dual arm. To achieve optimization motion in the task space, a redundancy resolution at velocity level has been implemented through neural-dynamics optimization. Extensive experiments have been made by a number of subjects, and the results were provided to demonstrate the effectiveness of the proposed control strategy.